Analysis of the Relationship between Nutritional Knowledge and Nutritional Status - Syafii Syafii (Musamus Journal of Physical Education and Sport (MJPES), 2023)
Objective. Nutrition is a crucial factor that significantly affects a person's overall health. A person's nutritional status is influenced by various factors, and one of them is their understanding of nutrition. In the wake of the COVID-19 pandemic, nutrition has become a hot research topic, especially for researchers who are also teachers. In this research, the independent variable would be the students' nutrition knowledge, whereas the dependent variable would be their nutritional status. The primary aim of this research is to establish the relationship between nutritional knowledge and nutritional status. The findings of this study could help in encouraging students to share their knowledge about nutrition with their family members and become advocates of good health practices. Materials and Methods. For this particular research study, a sample group of 50 students from class X of SMA Negeri 2 Merauke was selected using a purposive sampling technique to obtain accurate findings, the research employed quantitative research methods, specifically the Spearman Test, which aimed to test correlation. Result. The findings of the study indicate a Spearman rank correlation coefficient of 0.804, suggesting a strong correlation between the two variables under consideration. Moreover, the coefficient of determination analysis reveals that nutritional knowledge factors account for 38% of the variation in nutritional status, with the remaining 62% being influenced by other factors. These results underscore the importance of enhancing nutritional knowledge to improve nutritional status. Conclusion. Maintaining a healthy diet and lifestyle is crucial, especially during these times of the COVID-19 pandemic. While teachers at school play a significant role in imparting nutrition knowledge, it is the collective responsibility of everyone to prioritize healthy living. By doing so, we not only increase our fitness levels but also contribute to the overall quality of our family's economy. It is essential to recognize that nutrition knowledge is just one of the many factors that influence our well-being, but it is undoubtedly a crucial one.